Thin-wall ceramic tube for static pressure strength test and preparation method of thin-wall ceramic tube
By weaving or winding, molding, density and surface grinding of thin-walled ceramic tubes, the problem of difficulty in accurately detecting the annular strength of SiCf/SiC composite clad tubes in the prior art is solved, and the static pressure conditions are realized. Accurate strength test.
Patent Information
- Application Number
- CN202411384895.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to accurately characterize the annular strength of SiCf/SiC composite clad tubes, especially under static pressure conditions, and the thin-walled ceramic tubes are small in size, slender, poor in finish, brittle and porous, and internal pressure cannot be achieved. Real working condition intensity detection under the method.
Thin-walled ceramic tubes tested using static pressure strength, their prefabricated body is woven or wound, and is denser by chemical vapor deposition or pioneer impregnation and cracking. The surfaces at both ends are ground and enhanced to ensure airtightness and mechanical properties. .
The accurate characterization of the annular strength of ceramic tubes is achieved, and the problem of difficulty in achieving effective sealing of ceramic tube walls and tool fixtures during static pressure failure is solved, which improves the accuracy and reliability of the test.
Smart Images

Figure CN119437831A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cladding tube mechanical property testing, and relates to a thin-walled ceramic tube for static pressure strength testing and a preparation method thereof. Background Art
[0002] Accident Tolerant Fuel (ATF) has become the top priority for the safe development of nuclear power. Countries around the world are developing a new generation of cladding materials that can replace zirconium alloys. f SiC / SiC composite materials have attracted much attention due to their low density, high specific strength, high specific modulus, oxidation resistance, fatigue creep resistance, insensitivity to cracks, and no catastrophic damage. In addition, they still have good mechanical properties and thermal shock resistance under neutron irradiation and high temperature environment, especially after losing the coolant, they can still ensure the integrity of the cladding tube structure and improve the accident resistance. This makes SiC f / SiC composite materials have great application prospects in the nuclear field and have become ideal candidate materials for cladding of nuclear fuel elements and nuclear reactor control rods.
[0003] In order to ensure the safety and effectiveness of composite cladding tubes during operation, it is necessary to comprehensively characterize the performance of the cladding tubes, including mechanical properties, thermal conductivity, radiation resistance, hydrothermal corrosion resistance, etc. The mechanical performance tests mainly include the axial tensile performance and circumferential compressive performance of the cladding tubes. For the test of circumferential strength, the industry currently mainly uses expanding plug testing and circumferential tensile testing.
[0004] According to ASTM C1819-15, the circumferential strength of the cladding tube is tested by the expansion plug test. The elastomer uses a 95 hardness polyurethane plug, the test span is 10mm, the loading rate is 0.5mm / min, and the compression load-displacement data and curve of the polyurethane plug are recorded. Assuming that the pressure on the inner wall of the cladding tube is the same at all locations, the pressure Pi inside the cladding tube can be calculated by the formula. However, this method is more suitable for non-brittle materials such as metal cladding, and the performance of the polyurethane plug cannot be ignored.
[0005] Patent CN207717516U discloses a circumferential tensile testing device for silicon carbide cladding tubes, which can be used to conveniently and quickly conduct circumferential tensile tests on silicon carbide cladding tubes, obtain circumferential stress conditions, and achieve the purpose of accurate and rapid testing. This method causes stress concentration due to bending, resulting in low test results and large data dispersion.
[0006] Due to SiC f / SiC composite cladding tubes are brittle, and the above method applies uneven stress and cannot accurately simulate the actual working conditions of the cladding tube during operation. The static pressure blasting method can effectively improve the above problems. This method does not require high test piece shape, and the pressure can be evenly applied to the inner surface, thereby forming a stable tensile stress in the circumferential direction, and the data is more realistic. However, the static pressure method requires thin-walled ceramic pipes to be dense and have high dimensional accuracy.
[0007] Patent CN114057502A discloses a method for preparing a ceramic-based composite material slender thin-walled pipe fitting and a ceramic-based composite material slender thin-walled pipe fitting and application thereof. First, prepare C f / SiC or SiC f / SiC composite pipe fittings are used as the middle layer of the target pipe fittings; secondly, the middle layer of the processed ceramic matrix composite slender thin-walled pipe fittings is immersed in SiC whisker slurry for densification; secondly, SiC ceramic inner layer and SiC ceramic outer layer are respectively prepared on the inner wall and outer wall of the middle layer of the densified ceramic matrix composite slender thin-walled pipe fittings; finally, the prepared inner layer and outer layer of the pipe fittings are polished.
[0008] Patent CN107686364A discloses a nuclear fuel cladding tube and a preparation method thereof, wherein the tube wall comprises, from the inside to the outside, a first fiber-reinforced ceramic-based composite material layer, a second fiber-reinforced ceramic-based composite material layer and a ceramic layer, wherein the first fiber-reinforced ceramic-based composite material layer is composed of a first fiber preform and a first ceramic matrix filled in the pores of the first fiber preform; the second fiber-reinforced ceramic-based composite material layer is composed of a second fiber preform and a second ceramic matrix filled in the pores of the second fiber preform; the first fiber preform is formed by winding a fiber cloth impregnated with resin glue into a tube and then curing-carbonizing it, and the second fiber preform is formed by weaving a plurality of fiber bundles impregnated with resin glue and winding them on the circumference of a fiber cloth winding tube and then curing-carbonizing it; the ceramic layer is prepared by a chemical vapor deposition process.
[0009] However, the cladding tube made by the above patent is small in size, slender, poor in finish, brittle and porous, and it is impossible to use the internal pressure method that can simulate the actual working conditions of the cladding tube to conduct key circumferential strength testing. The reasons are as follows: the above patent cannot achieve precise processing and processing of the inner surface, cannot form a finish that meets the requirements, cannot install seals to match it to form a dynamic seal, and cannot guarantee the sealing requirements required for pressurization; the above patent cannot achieve reliable connection with larger-sized joints in the pressure system for testing strength; brittle materials are prone to failure due to random cracks when loaded by ordinary testing methods, cannot reflect the overall circumferential strength, and cannot truly test the strength; the cladding tube involved in the above patent has unacceptable pores in the strength test, and cannot achieve internal fluid medium pressurization to simulate the actual load-bearing, so the above patent cannot achieve the same internal pressure method as the actual working conditions for effective strength testing. Summary of the invention
[0010] The purpose of the present invention is to provide a thin-walled ceramic tube for static pressure strength testing and a preparation method thereof in order to overcome at least one defect of the above-mentioned prior art. The present invention realizes accurate characterization of the circumferential strength of the ceramic tube.
[0011] The purpose of the present invention can be achieved by the following technical solutions:
[0012] One of the technical solutions of the present invention is to provide a thin-walled ceramic tube for static pressure strength testing, the ceramic tube comprising a preform, both ends of the preform are provided with grinding sections;
[0013] Densifying the formed preform to obtain a ceramic tube, grinding the surfaces of both ends of the ceramic tube to obtain a thin-walled ceramic tube for static pressure strength testing;
[0014] The coaxiality of the two ends of the grinding shall not be greater than 0.2mm, and the surface finish shall be less than 0.2 to ensure the airtightness of the test process.
[0015] One of the technical solutions of the present invention is to provide a method for preparing the thin-walled ceramic tube for static pressure strength testing, the method comprising the following steps:
[0016] S1. Thin-walled ceramic tube preform forming,
[0017] Using a braiding machine or a winding machine to braid or wind carbon fiber or silicon carbide fiber on a cylindrical mandrel to obtain a tubular preform;
[0018] S2, densification of thin-walled ceramic tube preform,
[0019] The preform is densified by chemical vapor infiltration (CVI) or precursor impregnation pyrolysis (PIP) using chemical vapor deposition equipment or pressure impregnation equipment to ensure that no liquid infiltration occurs during the static pressure destruction process, thereby obtaining a composite thin-walled ceramic tube that meets the density requirements;
[0020] S3, grinding of the outer wall of thin-walled ceramic tube at both ends,
[0021] The surfaces of both ends of the ceramic tube are ground using a centerless grinder to ensure surface smoothness, thereby obtaining a thin-walled ceramic tube for static pressure strength testing.
[0022] Furthermore, in step S1, the tension of weaving or winding is 1-5N, the angle is 20-45°, and the number of layers is 1-5.
[0023] Furthermore, in step S1, the inner diameter of the preform is ≥4 mm, the outer diameter is ≤30 mm, the length is 150-6000 mm, and the tube wall thickness is 0.5-3 mm.
[0024] Furthermore, in step S2, the deposition gas for chemical vapor infiltration is methyltrichlorosilane, with a flow rate of 50-200 g / h, a temperature of 1000-1200° C., a pressure of 0.5-5 kPa, and a time of 100-400 h.
[0025] Furthermore, in step S2, the impregnation liquid for the precursor impregnation and cracking is polycarbosilane, the pressure is 0.5-5MPa, the time is 5-50h, the cracking temperature is 800-1000°C, the time is 2-8h, and the number of times is 3-5 times.
[0026] Furthermore, the density of the preform in step S2 is greater than 2.8 g / cm 3 .
[0027] Furthermore, for the convenience of clamping, the length of the grinding section in step S3 is 10-30 mm.
[0028] Furthermore, in step S3, the outer walls of both ends of the thin-walled ceramic tube are strengthened.
[0029] If the tube wall is too thin or the tube diameter does not match the O-ring for static pressure destruction, use a winding machine to strengthen the surfaces of both ends of the ceramic tube by winding carbon fiber, glass fiber or silicon carbide fiber.
[0030] Furthermore, the winding tension is 1-5N, the angle is 20-45°, until the tube wall thickness or tube diameter reaches the requirement, and the length of the reinforcement section is 10-30mm.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention is suitable for testing the annular strength of the pipe body by the static pressure method. The surface densification can solve the problem that it is difficult to achieve effective sealing between the ceramic pipe wall and the fixture during the static pressure destruction process, which is conducive to more accurately characterizing the mechanical properties of the pipe fittings;
[0033] (2) The present invention can make the thin-walled ceramic tube meet the requirements of static pressure failure through end surface grinding and appropriate reinforcement, thereby achieving accurate characterization of the circumferential strength of the ceramic tube. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of a thin-walled ceramic tube used for static pressure strength testing in an embodiment of the present invention.
[0035] Description of the markings in the figure:
[0036] 1—preform, 2—grinding section. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0038] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0039] Embodiment 1:
[0040] A thin-walled ceramic tube used for static pressure strength testing, such as Figure 1 As shown, it includes a preform 1, and grinding sections 2 are provided at both ends of the preform 1;
[0041] The formed preform 1 is densified to obtain a ceramic tube, and the surfaces of both ends of the ceramic tube are ground to obtain a thin-walled ceramic tube for static pressure strength testing.
[0042] A method for preparing a thin-walled ceramic tube for static pressure strength testing, the specific steps are as follows:
[0043] S1, forming a thin-walled ceramic tube preform 1,
[0044] The silicon carbide fiber is braided on a cylindrical core mold using a braiding machine, and a braiding program is designed. The braiding tension is 3N, the angle is 30°, the number of layers is 3, the inner diameter of the preform 1 is 10mm, the outer diameter is 12mm, the length is 4000mm, and the wall thickness is 1mm, thereby obtaining a tubular preform 1;
[0045] S2, densification of the thin-walled ceramic tube preform 1,
[0046] The preform 1 is densified by chemical vapor infiltration (CVI) using a chemical vapor deposition device. Methyltrichlorosilane is used as the deposition gas. The flow rate is 100 g / h, the temperature is 1100°C, the pressure is 2 kPa, and the time is 200 h, so that the density of the preform 1 is 2.9 g / cm 3 , ensuring that no liquid infiltration occurs during the static pressure destruction process, and obtaining a composite thin-walled ceramic tube that meets the density requirements;
[0047] S3, grinding of the outer wall of thin-walled ceramic tube at both ends,
[0048] Use a centerless grinder to grind the surfaces of both ends of the ceramic tube. For easy clamping, the length of grinding section 2 is 10 mm, so that the coaxiality of the two ends is 0.18 mm and the surface finish is 0.18. The surface smoothness is ensured to ensure the airtightness of the test process and obtain a thin-walled ceramic tube for static pressure strength test.
[0049] The static pressure strength test of the above ceramic tube is carried out in the following specific steps:
[0050] After the ceramic tube passes the test, it is installed on the static pressure strength breaking device according to the test procedures, ensuring that the outer surface of the grinding section 2 at both ends of the ceramic tube is tightly sealed with the O-type rubber ring and coaxially matched with the static pressure strength breaking device components. The pressure applied range is 0-4MPa, the test temperature is 23℃, and the test humidity is 56%.
[0051] The static pressure strength destruction device switch was turned on, and compressed liquid was introduced. The pressure increased to 3.6 MPa, water droplets seeped out of the outer surface of the ceramic tube, and microcracks appeared in the middle. The failure met the requirements of the specification. After data processing, the test obtained that the circumferential strength of the ceramic tube sample in Example 1 was 280 MPa.
[0052] Embodiment 2:
[0053] A thin-walled ceramic tube for static pressure strength testing and a preparation method thereof are basically the same as Example 1, except that in step S1, the braiding angle is 45°, the number of layers is 1, the inner diameter of the preform 1 is 10 mm, the outer diameter is 11 mm, and the wall thickness is 0.5 mm. Before step S3, a carbon fiber-wound reinforcement section is added to the two end surfaces of the ceramic tube, that is, the outer walls of the thin-walled ceramic tube at both ends are reinforced. If the tube wall is too thin or the tube diameter does not match the O-ring for static pressure destruction, a winding machine is used to reinforce the two end surfaces of the ceramic tube by winding carbon fibers, the winding tension is 3N, the angle is 20°, until the tube wall thickness or tube diameter meets the requirements, that is, the inner diameter of the preform 1 is 10 mm, the outer diameter is 12 mm, the tube wall thickness is 1 mm, and the length of the reinforcement section is 10 mm.
[0054] The static pressure strength test of the above-mentioned ceramic tube is basically the same as that of Example 1, except that when compressed liquid is introduced, the pressure increases to 3.5MPa, water droplets seep out of the outer surface of the ceramic tube, microcracks appear in the middle position, and the failure meets the requirements of the specification. After data processing, the test obtains that the circumferential strength of the ceramic tube sample in Example 2 is 272MPa.
[0055] Embodiment 3:
[0056] A thin-walled ceramic tube for static pressure strength testing and a preparation method thereof are basically the same as Example 1, except that the chemical vapor deposition equipment CVI used in step S2 is replaced by a pressure impregnation equipment precursor impregnation pyrolysis (PIP), the impregnation liquid is polycarbosilane, the pressure is 2.5 MPa, the time is 24 hours, the pyrolysis temperature is 9000°C, the time is 4 hours, and the number of times is 4 times.
[0057] The static pressure strength test of the above-mentioned ceramic tube is basically the same as that of Example 1, except that when compressed liquid is introduced, the pressure increases to 2.5MPa, water droplets seep out of the outer surface of the ceramic tube, microcracks appear in the middle position, and the failure meets the requirements of the specification. After data processing, the test obtains that the circumferential strength of the ceramic tube sample in Example 2 is 194MPa.
[0058] Embodiment 4:
[0059] A thin-walled ceramic tube for static pressure strength testing and a preparation method thereof are basically the same as those in Example 1, except that in step S1, the silicon carbide fiber is replaced by carbon fiber, and weaving using a braiding machine is replaced by winding using a winding machine.
[0060] The static pressure strength test of the above ceramic tube is carried out in the following specific steps:
[0061] After the ceramic tube passes the test, it is installed on the static pressure strength breaking device according to the test procedures, ensuring that the outer surface of the grinding section 2 at both ends of the ceramic tube is tightly sealed with the O-type rubber ring and coaxially matched with the static pressure strength breaking device components. The pressure application range is 0-2MPa, the test temperature is 23℃, and the test humidity is 56%.
[0062] The static pressure strength destroying device switch was turned on, and compressed liquid was introduced. The pressure increased to 1.7 MPa, and the outer surface of the ceramic tube cracked in the circumferential direction. The failure met the specification requirements. After data processing, the test obtained that the annular strength of the ceramic tube sample in Example 1 was 132 MPa.
[0063] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A thin-walled ceramic tube for static pressure strength testing, characterized in that: The ceramic tube comprises a preform (1), and grinding sections (2) are provided at both ends of the preform (1); Densifying the formed preform (1) to obtain a ceramic tube, and grinding the surfaces of both ends of the ceramic tube to obtain a thin-walled ceramic tube for static pressure strength testing; The coaxiality of the two ends of the grinding shall not be greater than 0.2mm, and the surface finish shall be less than 0.
2.
2. A method for preparing a thin-walled ceramic tube for static pressure strength testing as claimed in claim 1, characterized in that: The method comprises the following steps: S1, forming a thin-walled ceramic tube preform (1), Using a braiding machine or a winding machine, carbon fiber or silicon carbide fiber is braided or wound on a cylindrical mandrel to obtain a tubular preform (1); S2, densification of the thin-walled ceramic tube preform (1), Using chemical vapor deposition equipment or pressure impregnation equipment to densify the preform (1) by chemical vapor infiltration or precursor impregnation cracking to obtain a composite material thin-walled ceramic tube; S3, grinding of the outer wall of thin-walled ceramic tube at both ends, The surfaces of both ends of the ceramic tube were ground using a centerless grinder to obtain thin-walled ceramics for static pressure strength testing.
3. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: In step S1, the tension of weaving or winding is 1-5N, the angle is 20-45°, and the number of layers is 1-5.
4. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: In step S1, the inner diameter of the preform (1) is ≥4 mm, the outer diameter is ≤30 mm, the length is 150-6000 mm, and the tube wall thickness is 0.5-3 mm.
5. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: In step S2, the deposition gas for chemical vapor infiltration is methyltrichlorosilane, with a flow rate of 50-200 g / h, a temperature of 1000-1200° C., a pressure of 0.5-5 kPa, and a time of 100-400 h.
6. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: In step S2, the impregnation liquid for the precursor impregnation cracking is polycarbosilane, the pressure is 0.5-5MPa, the time is 5-50h, the cracking temperature is 800-1000°C, the time is 2-8h, and the number of times is 3-5 times.
7. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: The density of the preform (1) in step S2 is greater than 2.8 g / cm 3 .
8. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: The length of the grinding section (2) in step S3 is 10-30 mm.
9. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 2, characterized in that: Step S3: The outer walls of both ends of the thin-walled ceramic tube are strengthened. The surfaces of both ends of the ceramic tube are reinforced by winding carbon fiber, glass fiber or silicon carbide fiber using a winding machine.
10. The method for preparing a thin-walled ceramic tube for static pressure strength testing according to claim 9, characterized in that: The winding tension is 1-5N, the angle is 20-45°, and the length of the reinforcement section is 10-30mm.
Citation Information
Patent Citations
Nuclear fuel cladding pipe and preparation method thereof
CN107686364A
Tensile detection device of carborundum cladding tube hoop
CN207717516U
Cited By
High-strength winding thin-wall SiC composite cladding tube and preparation method thereof
CN121331519A